Evaluation of in vitro production rates of bovine embryos using melatonin-supplemented culture medium - Magalhães, Ricardo (2021)
In this study, we aimed to evaluate the rate of bovine embryo production by using 50 ng/mL melatonin supplementation in in vitro culture medium. For this, oocytes from slaughterhouse ovaries were matured in vitro in TCM-199 medium with Earle’s balanced salt solution + 10% SFB, FSH, and LH in an atmosphere of 5% CO2. Twenty-four hours after IVM, the oocytes underwent in vitro fertilization in human tubal fluid under the same conditions as above, for 18 h. Semen was fractionated by Percoll gradient centrifugation and the concentration of sperm was adjusted to 1 × 106/mL. Probable zygotes were then divided into two groups: the control group grown in drops of 90 μL SOFaa medium + 0.6% BSA + 2.5% SFB, in an atmosphere of 5% CO2, 90% N2, and a melatonin group (Mel), similarly cultured in 90 μL drops of SOFaa medium + 0.6% BSA + 2.5% SFB + 50 ng/mL melatonin. Cleavage rates were assessed on day 3 (D3). On D7, blastocyst formation rates were evaluated. Eight routines were performed (320 oocytes per routine). Data were analyzed with ANOVA, followed by Tukey’s range test using a general linear model. The level of statistical significance was set at 5%. There were no differences in the rates of cleavage or blastocyst formation between the control and melatonin groups (P > 0.05). Thus, under the conditions used in this study, supplementation with melatonin did not yield benefits in increasing the rate of in vitro bovine embryo production.